EKSPLORASI DESAIN BUSANA PESTA WANITA BERBASIS INTERPRETASI LEGENDA PUTRI JUNJUNG BUIH DENGAN KAIN SASIRANGAN - Mayzahro Nuzulailatul Badriyah; Purwosiwi Pandansari sari (SINERGI : Jurnal Riset Ilmiah, 2026)
This research explores the creation of women’s party wear using Sasirangan as an Indonesian heritage textile (wastra). Although Sasirangan shares resist-dyeing characteristics with Batik, it is distinguished by its basting stitch technique (jelujur). Despite its development in contemporary fashion, designs that explicitly visualize the narrative of Princess Junjung Buih remain limited. This study aims to create a statement piece integrating the Ombak Sinampur Karang motif to represent the legend’s aesthetic and philosophical values. A descriptive qualitative creation method was applied through the stages of exploration, design, and realization, using design semiotics theory to transform narrative elements into contemporary visuals. Tailoring techniques convey a regal structure, while draping represents the water foam symbolizing the princess’s emergence. The results show that the “Deep Azure Essence” design successfully expresses Banjar cultural identity in modern fashion. Feasibility testing by three experts yielded an average score of 4.58 (“Highly Feasible”), with the highest score in the semiotics and cultural aspect (4.73). This study highlights local textile-based fashion innovation as a strategic effort in preserving South Kalimantan’s culture.